2017
DOI: 10.4236/ce.2017.88096
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Movies on the Affective Filter and English Acquisition of Low-Achieving English Learners

Abstract: This paper reports on the effects of movies on the acquisition of English language among students at a tertiary institution in Malaysia. In this study, "out-of-class" activities are leisure activities that students do outside classroom setting and watching movie is one example. The study aims to examine the effects of movies on the students' Affective Filter (i.e. motivation, anxiety, and self-confidence). The Affective Filter is a mental block that prevents language learners from being receptive towards compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 21 publications
4
17
0
Order By: Relevance
“…Furthermore, the number of studies on foreign language listening anxiety is very limited. However, the findings obtained in this study have similarity with the limited scientific sources (Ebrahimi & Bazaee, 2016;Nadrag & Buzarna-Tihenea, 2017;Parisi & Andon, 2016;Sirmandi & Sardareh, 2016) and studies (Kim, 2002;Lynch, 1998;Melanlıoğlu, 2013;Nath, Mohamad & Yamat, 2017;Wang, 2015) in the literature Based on the scientific data revealing the relationship between anxiety and using authentic materials, academic achievement, motivation, participation in activities, learning effort and self-confidence, the findings of using authentic videos in reducing the foreign language listening anxiety can be interpreted as follows: Authentic materials play an effective role in the development of students' listening skills, as a result of this, their academic achievement levels increase, and in parallel with the increase in academic achievement, the students' learning motivations, learning efforts and self-confidence levels increase, too. As a result, this increase leads to a decrease in foreign language listening anxiety.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, the number of studies on foreign language listening anxiety is very limited. However, the findings obtained in this study have similarity with the limited scientific sources (Ebrahimi & Bazaee, 2016;Nadrag & Buzarna-Tihenea, 2017;Parisi & Andon, 2016;Sirmandi & Sardareh, 2016) and studies (Kim, 2002;Lynch, 1998;Melanlıoğlu, 2013;Nath, Mohamad & Yamat, 2017;Wang, 2015) in the literature Based on the scientific data revealing the relationship between anxiety and using authentic materials, academic achievement, motivation, participation in activities, learning effort and self-confidence, the findings of using authentic videos in reducing the foreign language listening anxiety can be interpreted as follows: Authentic materials play an effective role in the development of students' listening skills, as a result of this, their academic achievement levels increase, and in parallel with the increase in academic achievement, the students' learning motivations, learning efforts and self-confidence levels increase, too. As a result, this increase leads to a decrease in foreign language listening anxiety.…”
Section: Discussionsupporting
confidence: 87%
“…Similarly, Atas (2014) found that the intervention of drama in learning English does help to lower the speaking anxiety of learners. A recent study conducted by Nath, Maslawati and Hamidah (2017) also corroborated this finding. They studied about movies that are akin to creative drama and they found that movies do reduce learners' specifically the low achievers' affective filter in learning English language.…”
Section: Krashen's Affective Filter Hypothesissupporting
confidence: 67%
“…This hypothesis is based on the notion that input is filtered according to learners' moods. Affective variables such as motivation, self-confidence, and anxiety play a role in second language acquisition (Kakule, 2016;Krashen, 1982;Nath et al, 2017). These variables shape the success of second language acquisition as Du (2009) and Krashen (1982) have pointed out.…”
Section: Krashen's Affective Filter Hypothesismentioning
confidence: 99%
“…The idea is to eliminate a stressful atmosphere by using relaxed and fun activities to motivate learners and lower the affective filter (Abukhattala, 2013;Kakule, 2016). Nath et al (2017) have argued that outdoor activities are most effective for doing so. Groupwork and social activities are also important since they lower anxiety and boost confidence (Du, 2009).…”
Section: Krashen's Affective Filter Hypothesismentioning
confidence: 99%